2011
DOI: 10.1074/jbc.m111.270710
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein δ Mediates Tumor Necrosis Factor α-induced Aurora Kinase C Transcription and Promotes Genomic Instability

Abstract: Epidemiologic and clinical research indicates that chronic inflammation increases the risk of certain cancers, possibly through chromosomal instability. However, the mechanism of inflammation-dependent chromosomal instability associated with tumorigenesis is not well characterized. The transcription factor CCAAT/enhancer-binding protein ␦ (C/EBP␦, CEBPD) is induced by tumor necrosis factor ␣ (TNF␣) and expressed in chronically inflamed tissue. In this study, we show that TNF␣ promotes aneuploidy. Loss of CEBPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…These genes were not expressed in EAC. Wu et al stated that AURKC was overexpressed in inflamed cervical tissue specimens and HDAC inhibitors are therapeutic for several inflammatory conditions (38,39). Do these genes have a role in addition to defect of the defense mechanism of the esophagus in patients with EE in gastroesophageal disease?…”
Section: Discussionmentioning
confidence: 99%
“…These genes were not expressed in EAC. Wu et al stated that AURKC was overexpressed in inflamed cervical tissue specimens and HDAC inhibitors are therapeutic for several inflammatory conditions (38,39). Do these genes have a role in addition to defect of the defense mechanism of the esophagus in patients with EE in gastroesophageal disease?…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ischemia has also been reported (Wen et al, 2004a) to induce aberrant neuronal cell cycle re-entry that can be reduced by 17␤-estradiol, an inhibitor of TNF (Hsu et al, 2000), a cytokine with a long history of interfering with mitosis (Darzynkiewicz et al, 1984) and more recently demonstrated to cause aneuploidy (Wu et al, 2011), the phenomenon that sets the scene for aberrant cell cycling and thus apoptosis. As recently reviewed by Clark et al (2010), trauma triggers release of inflammatory cytokines through the action of mitochondrial DNA set free from disrupted cells .…”
Section: The Broader Picture-stroke Traumatic Brain Injury and Imentioning
confidence: 99%
“…Another approach, based on synthesizing GLP-1 analogs, has led to other subcutaneous agents, such as liraglutide (Buse et al, 2009). Both of these types of GLP-1 mimetics pass through the blood-brain barrier and have proved to be strikingly active against AD models (Perry et al, 2003;Liu et al, 2009;Porter et al, 2010;Li et al, 2011;McClean et al, 2011) as well as against a model of the cognitive defects in T2DM . Recent basic studies give impressively detailed reinforcement to this approach (Bomfim et al, 2012;Talbot et al, 2012).…”
Section: E Glucagon-like Peptide-1 Mimetics and Dipeptidyl Peptidasementioning
confidence: 99%
“…However, unlike the inflammatory effectors NF-kB and STAT3 that are consistently activated in cancer cells, CEBPD inactivation has been observed in several types of cancer, including cervical and hepatocellular carcinoma (10,14), breast (15), prostate cancer (9), and leukemia (16). In addition to acting as a tumor suppressor, several recent reports have suggested that CEBPD plays an oncogenic role under certain conditions (17,18). Furthermore, CEBPD attenuation can sensitize CDDPinduced cell death in CDDP-resistant UCUB cells (19).…”
Section: Introductionmentioning
confidence: 99%